Hunger and Revolution: A New Reading of Virgilio Piñera's El flaco y el gordo - Anderson, Thomas F. (Latin American Theatre Review, 2005)
El flaco y el gordo (1959), the first literary work that Virgilio Piñera wrote after the triumph of the Revolution, is, above all, a fierce criticism of the social problem of hunger in pre-revolutionary Cuba. In this essay I argue that many critics, who seem to have been overly eager to read a text written during such an important moment in Cuban history as either categorically pro or antirevolutionary, have erroneously insisted that Piñera’s play is negative and fatalistic, and that it underscores his skepticism and his lack of confidence in the Revolution from the beginning. Such interpretations misconstrue not only Piñera’s view of the Revolution, but also the play’s central message and the author’s primary motivation for writing it. Well aware that Cuba’s chronic hunger had helped to make Fidel Castro’s menu for change more palatable for so many, Piñera chose to use this familiar form of suffering in Cuba as a central metaphor in the play. (TFA)